Effect of electrostatically charged and neutral polysaccharides on the rheological characteristics of peanut protein isolate after high-pressure homogenization. (April 2018) - Jiao, Bo; Shi, Aimin; Liu, Hongzhi; Sheng, Xiaojing; Liu, Li; Hu, Hui; Adhikari, Benu; Wang, Qiang
Abstract: Peanut protein is attracting increased research and application interest because of its high nutritional value and its functional properties. In this study, two different electrostatically charged (chitosan and xanthan gum) polysaccharides and a neutral polysaccharide (guar gum) were used to investigate the interactions between polysaccharides and peanut protein isolate (PPI) in an aqueous medium after high-pressure homogenization. The rheological properties of the polysaccharides, PPI, and polysaccharide-PPI mixtures were characterized by continuous shear, frequency sweep, and temperature sweep measurements. The shear viscosity of the homogenized samples followed a power law model (R 2  ≥ 0.992). High-pressure homogenization changed the continuous shear characteristics of the xanthan gum solution and the PPI-xanthan gum mixture. The continuous shear characteristics of PPI-chitosan and PPI-guar gum mixtures were altered by high-pressure homogenization at higher PPI concentrations (15% w/w). The storage moduli (Gʹ) of the mixed homogenates were frequency-dependent. High-pressure homogenization did not alter the elastic properties of the pure PPI suspension. However, the Gʹ changed in all three PPI-polysaccharide mixtures after high-pressure homogenization. Typical gel setting, gel weakening, and gel strengthening phases were observed in all the mixed homogenates except for the PPI-xanthan gum mixture, which did not show gel weakening. High-pressure homogenization changed the gelling time for most samples and induced gel weakening behavior in the PPI-xanthan gum mixture when the temperature was increased. Graphical abstract: Image 1 Highlights: Three different peanut protein isolate-polysaccharide mixtures were investigated. The shear viscosity of all the samples followed Power law model well. The storage and loss moduli of all the mixtures were frequency dependent. High-pressure homogenization (HPH) changed the gelling time in most samples. HPH induced gel weakening behavior in peanut protein isolate-xanthan gum mixture.